2015
DOI: 10.3390/pathogens4030626
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Detection and Characterization of Theileria Infecting Wildebeest (Connochaetes taurinus) in the Maasai Mara National Reserve, Kenya

Abstract: Theileria is a genus of tick-borne protozoan that is globally widespread and infects nearly all ungulates in which they cause either latent infection or lethal disease. Wild animals are considered reservoir hosts of many species of Theileria and their diversity in wildlife species is increasingly becoming of interest. The molecular characterization and identification of Theileria infecting wildlife has been studied in a few species including buffalo, which are considered reservoir host for Theileria parva infe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 49 publications
(63 reference statements)
0
8
1
Order By: Relevance
“…(Berggoetz et al 2014) – in this study, only T. ovis was detected (51.3%). The study revealed T. ovis as the most prevalent pathogen, which is in contrast to previous studies (Mwamuye et al 2017; Omondi et al 2017; Wamuyu et al 2015) that did not detect this pathogen in Kenya. However, Adjou Moumouni et al (2015) reported this pathogen in cattle reared in the town of Ngong which is in Kajiado, a county bordering Machakos county in the south-west.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…(Berggoetz et al 2014) – in this study, only T. ovis was detected (51.3%). The study revealed T. ovis as the most prevalent pathogen, which is in contrast to previous studies (Mwamuye et al 2017; Omondi et al 2017; Wamuyu et al 2015) that did not detect this pathogen in Kenya. However, Adjou Moumouni et al (2015) reported this pathogen in cattle reared in the town of Ngong which is in Kajiado, a county bordering Machakos county in the south-west.…”
Section: Discussioncontrasting
confidence: 99%
“…In this study, a prevalence of 34.2% was detected for this pathogen – this is higher than previously reported in Kenya by Omondi et al (2017). However, this pathogen was not detected in the Maasai Mara and Shimba Hills National Reserves (Mwamuye et al 2017; Wamuyu et al 2015) located in the south-west of Kenya about 150 km from the study areas. Data from other studies in Africa showed a high prevalence of A. ovis in Tunisia (Belkahia et al 2014), Algeria (Aouadi 2017) and South Africa (Ringo et al 2018).…”
Section: Discussionmentioning
confidence: 89%
“…Theileria species were identified through the amplification of the 18S rRNA gene. The reaction conditions were 95 • C for 5 min, 30 cycles at 95 • C for 30 s, 54 • C for 30 s, 72 • C for 1 min, and a final extension of 72 • C for 9 min (Wamuyu et al, 2015).…”
Section: Molecular Detection Of Babesia and Theileria Sppmentioning
confidence: 99%
“…Human encroachment into wildlife sanctuaries has augment domestic-wildlife interactions thereby raising the risk margin for transmission of zoonotic diseases. Reduced interactions between human and wild animals by putting in place strict wildlife conservation and management legislations and strategic measures will reduce the burden of zoonotic disease transmission [37]. Population density in wildlife areas may occur in cases where management strategies include introduction of new animal species, which often result into introduction of new strains of zoonotic diseases, amidst improving number of animal population [38].…”
Section: Discussionmentioning
confidence: 99%
“…On average, up to 40% deaths occur in Africa due to infectious diseases, most of which are zoonotic [42]. These diseases have been reported to not only cause animal or human sickness but have led to deaths and major economic loses [37,43]. Echinococcosis, a neglected zoonotic disease, has been reported to have highest prevalence in Kenya [30,44].…”
Section: Discussionmentioning
confidence: 99%